Paraphrase detection of semantically equivalent text - Lim, Linus Ji Wei (2017)
This project aims to explore the possibility of using neural networks/machine learning to train language models to be able to understand and read semantically equivalent text that contains technical knowledge/esoteric terms related to computing and computer science. Furthermore, an additional exploration step will be to determine the feasibility of using said language models to understand semantically equivalent code patches and to tell them apart.